THE SYSTEM METHOD OF IMMERSION AND VIRTUALIZATION OF «MEASURED» SYSTEMS IN REAL PROCESS - Павлова, С.; Павлов, B.; Чепіженко, В. (Proceedings of National Aviation University (archive), 2012)
The system method of immersion and virtualization of «measured» systems in real process is offered. The method works out problem of virtual systems formation and sets conditions at which virtual object to become measuring system for of completely controlled condition field. Here the system of interactively oriented rectangular n-dimensional parallelepipeds is used as measuring system. Imbeddedness of measuring system in real process is understood as process of approximation of a real system controlled condition cone by system of rectangular n-dimensional parallelepipeds.